2003
DOI: 10.1089/109287503770736159
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Precipitation of Mineral Phases in Permeable Reactive Barriers

Abstract: The working lifetime of permeable reactive barriers (PRBs) using Fe 0 as the reactive media is limited by precipitation of secondary minerals, due to reaction of groundwater with Fe 0 . Since PRBs are emplaced at sites with widely differing groundwater chemistry, the suite of minerals that precipitate, as well as the rate of their formation, can vary widely. Using plausible phases obtained from field PRBs, the study shows that chemical equilibrium modeling can correctly predict the amounts of precipitates form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…Several researchers (Karvonen 2004;Komnitsas et al 2007;Li and Benson 2005;Liang et al 2003;McMahon et al 1999;Puls et al 1999a;Sarr 2001;Vogan et al 1999;Yabusaki 2001) have reported that armouring on the surface of reactive materials and chemical clogging of pores, by precipitated compounds during chemical reactions inside the PRB, decrease the long-term performance parameters such as reactivity, porosity and permeability. Significant concerns relating to precipitation of iron and aluminium oxides and hydroxides also exist in alkaline PRBs with acidic groundwater in ASS terrain because their solubilities are pH-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Karvonen 2004;Komnitsas et al 2007;Li and Benson 2005;Liang et al 2003;McMahon et al 1999;Puls et al 1999a;Sarr 2001;Vogan et al 1999;Yabusaki 2001) have reported that armouring on the surface of reactive materials and chemical clogging of pores, by precipitated compounds during chemical reactions inside the PRB, decrease the long-term performance parameters such as reactivity, porosity and permeability. Significant concerns relating to precipitation of iron and aluminium oxides and hydroxides also exist in alkaline PRBs with acidic groundwater in ASS terrain because their solubilities are pH-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Although encouraging treatment efficiency has been documented (Gu et al, 1998;Morrison et al, 2001;Su and Puls, 2003), reactions between ZVI and groundwater constituents causing ZVI corrosion and subsequent secondary mineral precipitation contribute to long term performance reduction of ZVI PRBs (Liang et al, 2003;Slater and Binley, 2003;Wilkin et al, 2003;Jin Suk et al, 2009). Carbonate minerals (often precipitated concurrent with iron oxides (Mackenzie et al, 1999;Phillips et al, 2000;Liang et al, 2003)), are known to significantly impact ZVI reactivity and hydraulic efficiency in systems with frequently encountered high carbonate groundwater conditions through surface passivation and pore clogging (Agrawal and Tratnyek, 1996;Phillips et al, 2000;Liang et al, 2003;Slater and Binley, 2003;Wilkin et al, 2003;Jeen et al, 2006;Jeen et al, 2007;Jin Suk et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…iron oxides or calcite) on the electrical responses. Yet PRB precipitate mineralogy is normally complex, being dependent on the groundwater chemistry at the site, in many cases including both iron oxides and calcite (Furukawa et al, 2002;Morrison et al, 2002;Liang et al, 2003;Phillips et al, 2003;Liang et al, 2005 and electronic (iron metal) conductors causing decreases in electrical conduction and polarization and, presumably, in surface reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Indraratna and Vafai (1997)). However, there are limited studies on the long-term performance of PRBs, especially with respect to chemical and/or biological clogging (Liang et al, 2003). Some researchers (e.g.…”
Section: Determination Of Prb Longevitymentioning
confidence: 99%